Sea Surface Temperature: From Observation to Applications - Francisco Pastor (MDPI AG, 2021)
Sea surface temperature (SST) has been defined by World Meteorological Organization (WMO) as one of the essential climate variables (ECVs) contributing to the characterization of Earth’s climate [...]